Risk-Based Supervision of Pension Funds in Australia - Thompson, Graeme (World Bank, Washington, DC, 2012)
This paper examines the development of risk-based supervision of pension funds in Australia. The large number of pension funds has meant that since the inception of pension fund supervision in the early 1990's the regulator has sought to identify high risk funds and focus its attention on these funds. However, the regulator developed a more sophisticated risk-rating model, known as PAIRS/SOARS, in 1992 in order to apply a more disciplined and consistent ratings methodology. Four reasons are given for the move towards more sophisticated risk-based supervision: 1) creation of an integrated supervisor which allowed the use of techniques used in banking and insurance to be adopted for pension fund; 2) the need to better use available supervisory resources; 3) several pension fund failures; and 4) concerns about industry weaknesses. Supervisory techniques used particularly in the banking industry, such as universal licensing, 'fit and proper' assessment, and risk management requirements were adopted for the pension sector between 2004 and 2006. The paper provides an outline of the PAIRS/SOARS risk-rating model which was also adopted. It observes that the approach provides an analytical discipline to risk assessment, strengthens the link between risk assessment and supervisory response, and allows better targeting of supervisory resources.